MS brain health quality standards: a survey on the reality in clinical practice in Germany - Isabel Voigt; Katja Akgün; Hernan Inojosa; Judith Haas; Herbert Temmes; Sven G. Meuth; Gavin Giovannoni; Tjalf Ziemssen (Neurological Research and Practice)
Abstract Background The quality of treatment is especially critical in the context of complex and chronic diseases such as multiple sclerosis (MS). The Brain Health Initiative, an independent international consortium of neurologists, reached a consensus on time-based quality standards prioritizing brain health-focused care for people with MS. Objectives To gain deeper insights into the transferability of these quality standards to a specific area, we conducted a survey among MS experts across various MS centers in Germany. Methods Participants were asked about time frames considered high standards and those currently being implemented in daily routine based on their experience. Results The results reveal a large gap between ideal conceptions and their adaptation in the real world, mostly due to a lack of resources. Conclusions Nevertheless, these guidelines and recommendations can be aspired to as ideals. Consensual and inclusive clinical pathways complemented by measurable quality indicators are needed to improve care and approach these ideals. Neither exists in the current management of MS.